Study of Land Characteristics in West Angkola and Marancar in Relation to the Fruit Quality of Salak Sidimpuan (Salacca sumatrana Becc.) - Wahyuni, Sri; Nasution, Yusriani; Pulungan, Sutan; Adelina, Rasmita; Lubis, Erwin Syah; Harahap, Sri Winaty (International Journal of Natural Science Studies and Development (IJOSS), 2025)
Salak Sidimpuan is one of the leading crops and is favored by the people of South Tapanuli due to its unique taste and fruit appearance compared to salak grown outside the region. This type of salak primarily grows in the central salak production areas, particularly in Angkola Barat and Marancar sub-districts. This study aims to identify the differences in land characteristics for salak cultivation in Angkola Barat and Marancar, and to determine the relationship between land characteristics and the fruit quality of Salak Sidimpuan. The research method employed a field survey and purposive sampling, a sampling technique based on specific criteria. Statistical analysis was performed using an independent samples t-test and linear regression with SPSS software. The results of the t-test showed that land characteristics such as organic carbon (C-organic), phosphorus (P), and total dissolved solids (TDS) of the fruit in Angkola Barat and Marancar did not differ significantly. However, cation exchange capacity (CEC), nitrogen (N), and fruit weight showed significant differences. Regression analysis revealed that C-organic, CEC, N, P, and potassium (K) had a positive correlation with fruit quality in Angkola Barat, with correlation coefficients of 0.079, 0.670, 0.041, 0.651, and 0.412, respectively.